Influence of grape maturity and maceration time on sensory characteristics and phenolics in Pinot noir and Cabernet-Sauvignon wines - Sandra Feifel; Daniel Zimmermann; Melanie Schaub; Pascal Wegmann-Herr; Elke Richling; Dominik Durner (OENO One, 2025)
Measures of grape phenolics have become important indicators to determine grape maturity, though varietal differences must be considered. The objective of this study was to determine whether maceration time can modulate the phenolic profile and sensory characteristics of wines produced from grapes of different maturities. Pinot noir and Cabernet-Sauvignon grapes were harvested at three different stages of grape maturity, in a range of 20–25 Brix, and vinified using 7-day and 14-day maceration times in experimental fermenters. Sensory evaluation and analysis of phenolic composition were carried out after bottling. The effect of maceration time was found to be different from the influence of grape maturity as shown by sensory evaluation and phenolic composition. Extended maceration neither compensated for grape immaturity nor enhanced the effects of immaturity. Changes in the phenolic composition with progressing grape maturity and extending maceration time were reflected in the wine colour as well as in taste and tactile ratings in the sensory evaluation of the wines. Skin-associated phenolics such as anthocyanins and polymeric pigments correlated with grape maturity, while extended maceration enhanced the extraction of seed-associated phenolics such as monomeric catechins, procyanidins and procyanidin gallates. The influences of grape maturity and maceration time on gallocatechins and prodelphinidins were different for Pinot noir and Cabernet-Sauvignon. The concept of “phenolic maturity” therefore requires a differentiated view on individual phenolic compounds, seed- and skin-associated phenols, and must take varietal differences into account. It is suggested that concentrations of anthocyanins and polymeric pigments are suitable indicators for grape maturity, whereas concentrations of monomeric catechins and procyanidins are good indicators for maceration time.